STUDI KRITIS LEGISLASI DALAM PERUNDANG-UNDANGAN PERBANKAN SYARIAH - Abul Khair (Al-Bayyinah, 2017)
AbstractThe presence of sharia banking in Indonesia is just beginning to develop, following the issuance of Law no. 21 of 2008 on sharia banking, although it has been discourse long before the issuance of the Act, which is more than half a century ago. The delay is due to two things. The first is due to political issues. The labeling of "sharia" in the name of banking institutions in the government's perspective, especially in the New Order regime, is seen as part of the concept of an Islamic state. Another obstacle is the issue of legal umbrella that does not yet exist, because the existing law at that time, namely Law no. 14 of 1967 concerning the Principle of Banking, requires the banking to run with the system of interest, while the interest system is seen as a system that is not Islamic. Herein lies the efforts of various Islamic circles to sharia banking legal umbrella can be realized. Periodically, various renewals are made in the concept of national banking. Religious institutions such as MUI, especially post-legitimacy and full authority to issue fatwa in the field of Islamic economics, succeeded in realizing the expectations of society until finally born a special law on sharia banking. But until now, the implementation of Islamic banking system still leaves a variety of problems and still need to be criticized.Kata Kunci: Legislasi, Perbankan Syariah.